Imaging With the Past: Revealing the Complexity of Chimaeroid Pelvic Musculature Anatomy and Development - Pears, Jacob B.; Tillett, Carley; Tahara, Rui; Larsson, Hans C. E.; Boisvert, Catherine A. (Frontiers in Ecology and Evolution, 2022)
Chondrichthyans are now widely adopted as models for examining the development and evolution of the stem gnathostome body plan. The fins of some cartilaginous fish are recognised for their plesiomorphic form and mode of muscular development, i.e. epithelial extension. Despite detailed molecular and descriptive examinations of these developmental mechanisms, there has been little contemporary examination of the ontogeny and morphology of the musculature in chondrichthyans including that of the paired fins. This gap represents a need for further examination of the developmental morphology of these appendicular musculatures to gain insight into their evolution in gnathostomes. The elephant shark is a Holocephalan, the sister group of all other chondrichthyans (Holocephali: Callorhinchus milii). Here, we use nano-CT imaging and 3D reconstructions to describe the development of the pelvic musculature of a growth series of elephant shark embryos. We also use historical descriptions from the 19th century and traditional dissection methods to describe the adult anatomy. This combined approach, using traditional methods and historical knowledge with modern imaging techniques, has enabled a more thorough examination of the anatomy and development of the pelvic musculature revealing that chimaeroid musculatures are more complex than previously thought. These data, when compared to extant and extinct sister taxa, are essential for interpreting and reconstructing fossil musculatures as well as understanding the evolution of paired fins.